2008
DOI: 10.1016/j.cellsig.2008.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The interferon-γ-mediated inhibition of lipoprotein lipase gene transcription in macrophages involves casein kinase 2- and phosphoinositide-3-kinase-mediated regulation of transcription factors Sp1 and Sp3

Abstract: The mechanisms underlying transcriptional inhibition by interferon-γ (IFN-γ) are poorly understood despite the existence of a large number of genes that are regulated in this manner and the key role of this cytokine in inflammatory disorders such as atherosclerosis. We have previously identified a novel mechanism for transcriptional inhibition by IFN-γ that involves a reduction in the binding of transcription factors Sp1 and Sp3 to regulatory sequences in the lipoprotein lipase (LPL) gene. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…For an individual IRepG (‘lipoprotein lipase’), negative regulation by SP1 and SP3 has been described (55). Our data imply that such regulation is more widespread than commonly accepted and thus deserves a thorough investigation concerning the underlying receptor-proximal events and contribution to antiviral, anti-pathogenic and anti-tumorigenic IFNγ functions.…”
Section: Resultsmentioning
confidence: 99%
“…For an individual IRepG (‘lipoprotein lipase’), negative regulation by SP1 and SP3 has been described (55). Our data imply that such regulation is more widespread than commonly accepted and thus deserves a thorough investigation concerning the underlying receptor-proximal events and contribution to antiviral, anti-pathogenic and anti-tumorigenic IFNγ functions.…”
Section: Resultsmentioning
confidence: 99%
“…The LPL enzyme expressed by macrophages has been shown to contribute to foam cell formation because of its ability to bind to both the cell surface and lipoproteins via different regions that cause the accumulation of the latter and their subsequent uptake by the cells (bridging action) [3, 4]. Interestingly, our previous studies had shown that PI3K is involved, at least in part, in the IFN-γ-mediated regulation of LPL expression [23] and this study extends this to its constitutive expression in human macrophages. In addition to receptor-mediated uptake of LDL, fluid-phase pinocytosis, particularly macropinocytosis, has recently been found to play an important role in the control of macrophage foam cell formation [5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of THP-1 monocytes into macrophages was performed for 24 h using 0.16 mM PMA, unless otherwise stated. Treatment of macrophages with IFN-g or the pharmacological inhibitors was as previously described (4,5).…”
Section: Cell Culturementioning
confidence: 99%
“…Several candidate kinases have been found to phosphorylate Ser 727 (1,3,4), although the exact roles of these remain poorly understood, particularly in macrophages in relation to atherosclerosis. Our previous studies have provided novel insights into IFN-g signaling and revealed critical roles for casein kinase 2 (CK2) and PI3K in the IFN-g-regulated expression in mouse macrophages of several key genes implicated in atherosclerosis (4,5). The action of both of these kinases was mediated, at least in part, through the regulation of STAT1 Ser 727 phosphorylation (4).…”
mentioning
confidence: 99%